Menguak dampak digitalisasi: kinerja karyawan dan kepuasan kerja di PT Millenium Pharmacon International Tbk. - Elizabeth Erena Putri Laskar; Agus Frianto (Universitas Negeri Surabaya, 2025)
This study aims to examine and explain the effect of digitalization on employee performance through job satisfaction. This research is classified as quantitative research with a population of 52 employees. This study uses Nonprobability Sampling technique, namely saturated sampling where all members of the population are sampled. This research applies Structural Equation Modeling (SEM) with the help of Smart Partial Least Square 3.2.9 software. The results of this study indicate that digitalization has a significant positive effect on employee performance, digitalization has no effect on job satisfaction, job satisfaction has no effect on employee performance, and job satisfaction can’t mediate the effect of digitalization on employee performance. This study highlights the importance of digitalization in the work environment, indicating that organizations need to adopt technology strategically to improve operational efficiency and work comfort. Overall, this study contributes to the understanding of how digitalization affects employee behavior and productivity by emphasizing the mediating role of job satisfaction in enhancing individual performance in organizations.